Tsunami Ready Community Facilitator Certified Internship at the Banjarnegara Geophysical Station - Fawwaz Atthoriq; Fharisa Nabila Rizvi; Ronal Kurniawan; Okta Rizal Karsih (Science, Technology, and Education Care, 2026)
Cilacap Regency is one of the regencies that serves as a disaster supermarket/laboratory. This means that Cilacap is at risk of disasters, including earthquakes, floods, landslides, and tsunamis. The objective is to assess community preparedness, specifically in the villages of Banjarsari and Nusawungu, and to prepare for earthquakes and tsunamis involving all components of society, both the government and the community itself, to achieve zero victims. This research was conducted from August to December 2023. Observations were made at the Banjarnegara Geophysical Station on Jalan Raya Banjarmangu Km. 12, Kalilunjar Village, Banjarmangu District, Banjarnegara Regency, Central Java. The method used in model the earthquake source mechanism was the P-wave first-impulse. The input to this system was waveform data from the InaTEWS network, which was entered via the internet using the Seedlink Protocol and then processed to enable automatic picking. The results were then used as input to determine the earthquake parameters and source mechanism in just a few seconds. Lightning observations are conducted using real-time recordings of atmospheric electrical events by the Lightning/2000 software, which are recorded in the format of atmospheric electrical event reports for one day, calculated from 00:00 to 24:00 local time. This is used to archive lightning event data for further processing in lightning mapping. The Tsunami Ready Community is a program to enhance community capacity in facing tsunami threats based on 12 indicators established by UNESCO-IOC. The hope is that the community will always be prepared and not be caught off guard in facing earthquake and tsunami threats